Crustal Configuration and Seismic Stability of the Eastern Indian Shield and Adjoining Regions: Insights for Incidents of Great Earthquakes in the Nepal-Bihar-Sikkim Himalaya - Singh, Rashmi; Khan, Prosanta Kumar (Frontiers in Earth Science, 2021)
The Eastern Indian Shield (EIS) comprises the intracratonic (coal-bearing) Damodar Gondwana basin, rift-controlled extensional Lower Gangetic basin (LGB), and the downward flexed Indo-Gangetic basin (IGB). The present study involves the computations and mapping of the basement configuration, sediment thickness, Moho depth, and the residual isostatic gravity anomaly, based on 2-D gravity modeling. The sediment thickness in the area ranges between 0.0 and 6.5 km, and the Conrad discontinuity occur at ~ 17.0 - 20 km depth. The depth of the Moho varies between 36.0 and 41.5 km, with the maximum value beneath the Upper Gangetic basin (UGB), and the minimum of ~ 36 km (uplifted Moho) in the south-eastern part beneath the LGB. The maximum residual isostatic anomaly of + 44 mGal in the southern part indicates the Singhbhum shear zone, LGB and Rajmahal trap to be under-compensated, whereas the northern part recording the minimum residual isostatic anomaly of – 87.0 mGal is over-compensated. Although the region experienced few moderate-magnitude earthquakes in the past, small-magnitude earthquakes are sparsely distributed. The basement reactivation was possibly associated with few events of magnitudes more than 4.0. Towards south, in the Bay of Bengal (BOB), seismic activities of moderate size and shallow origin are confined to the aseismic 85°E and 90°E ridges. The regions on the extreme north and south (along the Himalaya and the equatorial Indian Ocean, EIO) are experiencing moderate-to-great earthquakes over different times in the historical past, but the intervening EIS and the BOB have seismic stability. We propose that the two aseismic ridges are guiding the lithospheric stress fields, which are being further focused by the basement of the EIS, the BOB and the N-S extended regional fault-systems into the bending zone of the penetrating Indian lithosphere beneath the Himalaya. The minimum obliquity of the Indian plate and the transecting fault-systems in the foothills of the Himalaya channelize and enhance the stress field into the bending zone. The enhanced stress generates great earthquakes in the Nepal-Bihar-Sikkim Himalaya, and on being reflected back through the apparently stable EIS and BOB, the stress field creates deformation and great earthquakes in the EIO.